2006
DOI: 10.5194/hess-10-769-2006
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of dominant hydrological processes in a tropical catchment in a monsoonal climate via the downward approach

Abstract: Abstract. This study explores the dominant processes that may be responsible for the observed streamflow response in Seventeen Mile Creek, a tropical catchment located in a monsoonal climate in Northern Territory, Australia. The hydrology of this vast region of Australia is poorly understood due to the low level of information and gauging that are available. Any insights that can be gained from the few well gauged catchments that do exist can be valuable for predictions and water resource assessments in other … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Moreover, the advantages of this model lie primarily in its generalizable structure (water-balance type), its landscape-specific considerations (saturation-excess), its simple-routing method with minimal parameters (Jakeman & Hornberger, 1993;Montanari, Sivapalan, & Montanari, 2006;Perrin, Michel, & AndrĂ©assian, 2001), its model efficiency on the daily time step (Tilahun, Guzman, et al, 2013a;Tilahun, Mukundan, et al, 2013b), and its basis in processes observed in Ethiopia versus empiricism from the United States or Europe (Burt & McDonnell, 2015). It therefore provides an effective governing equation approach on a catchment scale based on a reduced form, direct field measurements spanning a range of scales, and theoretical studies (Burt & McDonnell, 2015;Kirchner, 2006).…”
Section: Modeling Approaches: Available Modelsmentioning
confidence: 99%
“…Moreover, the advantages of this model lie primarily in its generalizable structure (water-balance type), its landscape-specific considerations (saturation-excess), its simple-routing method with minimal parameters (Jakeman & Hornberger, 1993;Montanari, Sivapalan, & Montanari, 2006;Perrin, Michel, & AndrĂ©assian, 2001), its model efficiency on the daily time step (Tilahun, Guzman, et al, 2013a;Tilahun, Mukundan, et al, 2013b), and its basis in processes observed in Ethiopia versus empiricism from the United States or Europe (Burt & McDonnell, 2015). It therefore provides an effective governing equation approach on a catchment scale based on a reduced form, direct field measurements spanning a range of scales, and theoretical studies (Burt & McDonnell, 2015;Kirchner, 2006).…”
Section: Modeling Approaches: Available Modelsmentioning
confidence: 99%
“…For inference of the hydrological processes, multiple techniques are used, such as hydrometric data (e.g. Kirkby, ; McDonell, ; Bonell, ; Montanari et al , ), isotopical tracers (e.g. Dincer et al , ; Niemi, ; Payne and Schroeter, ; Sklash and Farvolden, ; Maloszewski et al , ; Turner et al , ; Buttle, ; Mortatti et al , ), chemical tracers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Uhlenbrook and Hoeg, 2003), tropical studies agree on the importance of fast flow components (different terms, listed in Table 1). Despite this agreement, the dominant processes continue to be among the most difficult and least understood ones (Montanari et al, 2006). Table 1 also shows the lack of attention to areas that receive < 2000 mm annual rainfall and are characterized by bimodal rainfall distribution with a distinct dry season (rainfall ≀ 20 mm month −1 ).…”
Section: Introductionmentioning
confidence: 99%